DEVELOPMENT OF STUDENTS’ KNOWLEDGE OF INFORMATION BASED ON MODELING OF COMPUTER NETWORKS - Fayzieva , Shohista ("Science Shine" International scientific journal, 2024)
This article explores how modeling computer networks enhances students’ understanding of information technology concepts. It examines various modeling techniques and their effectiveness in educational settings.